Mathematical analysis and application of a cholera transmission model with waning vaccine-induced immunity - Bai, Ning; Song, Chenwei; Xu, Rui (Nonlinear analysis: real world applications, 2021)
In this paper, a cholera infection model with vaccination is investigated, in which hyperinfectious and hypoinfectious vibrios, both human-to-human and environment-to-human transmission pathways, and waning vaccine-induced immunity are considered. The basic reproduction number is calculated and verified to be a threshold determining the global dynamics of the model. In addition, an application is demonstrated by investigating the cholera outbreak in Somalia, and the relevant control measures in the short term are given by elasticity and sensitivity analysis.